Kontribusi Kekuatan Otot Kaki dan Teknik Dasar Shooting Terhadap Akurasi Shooting Sepak Bola - Tayo Taufik Nurkirom; Indra Safari; Aam Ali Rahman (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the contribution of leg muscle strength and basic shooting technique skills to soccer shooting accuracy, both partially and simultaneously, and to determine the more dominant variable. The method used is quantitative research with a nonparametric regression approach. The study sample consisted of 25 soccer players aged 13-15 years who were selected using a purposive sampling technique. The research instruments included a vertical jump test to determine leg muscle strength, a test of basic shooting techniques and shooting accuracy. Data were analyzed using descriptive statistics and regression tests at a significance level of 5%. The results showed that simultaneously, leg muscle strength and basic shooting technique skills significantly influenced shooting accuracy with a significance value of 0.000. Partially, leg muscle strength had a significant effect with a significance value of 0.00, while basic shooting technique skills did not have a significant effect with a significance value of 0.384. Thus, leg muscle strength is a more dominant variable in influencing shooting accuracy. Keywords: Shooting Accuracy, Leg Muscle Strength, Football, Basic Shooting Techniques